Online Applied Problem-Based Learning to Determine the Shelf Life of an on-Site Solution of Refrigerated Drug - Vargas-Rodriguez, Yolanda Marina; Valdivia, Adolfo Eduardo Obaya; Montano-Osorio, Carlos; Lima-Vargas, Alvaro E; Pacheco-Ortin, Sandy M.; Vargas-Rodriguez, Guadalupe I. (International Journal of Educational Technology and Learning, 2020)
A problem-based online learning (PBe-L) teaching sequence was designed for calculating the shelf life (expiration date) of an on-site solution of refrigerated drug as part of activities of a Pharmaceutical Physical Chemistry course of Pharmacy major at FES Cuautitlán UNAM in Mexico. The teacher presents students the problem, a group collaborative activity is carried out to search for information in PBL cycles. Students are then shown a virtual experiment that includes experimental results. Another group collaborative activity is carried out for the search of information, for the procedural analysis of the results. Applying knowledge and understanding of the topics of chemical kinetics, temperature effect on the rate of chemical reactions and drug degradation reactions, etc., students solve the problem. Hake’s factor was determined for the conceptual gain. A Likert-type satisfaction survey was conducted and compared to the results of a group that was applied to the PBL strategy in person. At the end of the sequence students achieved recognition, comprehension and application learnings and conceptual gain was high. Allowing an integration of its cognitive framework of kinetics topics.